THE EFFECTIVENESS STAD COOPERATIVE LEARNING MODELS ON CRITICAL THINKING ABILITY AND STUDENT LEARNING OUTCOMES ON CHEMICAL EQUILIBRIUM - Rokhim, Deni Ainur; Widarti, Hayuni Retno; Permatasari, Anggun (UNESA Journal of Chemical Education, 2023)
Empirical research has informed that chemical equilibrium learning in chemistry class includes as a difficult subject for senior high school students, and the learning approach that can challenge this complexity in the Indonesian schooling context seems sparse. Therefore, this present study was designed to find out: (1) the implementation of STAD learning model in the chemistry class discussing chemical equilibrium topic and (2) the differences in the ability to think critically and learning outcomes of Indonesian senior high school students after being taught using STAD and conventional learning models. To collect and analyze the data, Posttest Only Control Design was employed. Findings suggested that (1) the implementation of STAD learning model had an average of 93% and conventional learning of 90%, (2) there are differences in the critical thinking abilities of students who were taught using STAD model (86.14%) higher than those taught using conventional learning model (71.14%), and (3) there are differences of students who were taught using STAD model (86.00%) higher than those taught using conventional learning model (81.76%). Based on these results, we can infer that STAD learning model could enhance students’ critical thinking abilities and learning outcomes effectively.